PKA direction on the primary radiation damage of tungsten by molecular dynamics simulations - Zhu, Fei; Tao, Junjie; Pei, Yaowu; Wu, Ziyi; Xiao, Tengyue; Song, Ligang; Wang, Dong; Ma, Xianfeng (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2026)
Molecular dynamics simulations were used to explore the impact of the direction of primary knock-on atom (200 keV) on the primary radiation damage in tungsten at various temperatures. The 〈110〉 PKA direction induces lower radiation damage, evident from the lower number of surviving Frenkel pairs, reduced interstitial/vacancy clustering fractions, lesser defects in large-sized clusters, and shorter dislocation lengths. The reduced damage in the 〈110〉 direction is attributed to its elevated probability of sub-cascades formation. The formation processes and mechanisms of different types of dislocations have been discussed. Mixed interstitial loops exhibit two distinct 〈100〉 fragment formation pathways. This study reveals three formation mechanisms for 〈100〉 interstitial loops: migrating 1/2〈111〉 loop interactions (primary), punch-out mechanism (secondary), and 1/2〈111〉→〈100〉 transformation through shear loop nucleation/propagation (tertiary). The 〈100〉 vacancy dislocations arise from the collapse of vacancy cluster. These findings provide critical insights into anisotropic radiation damage behavior and defect evolution mechanisms in tungsten.